RAISING AS A FREE SYNTACTIC OPERATION: EVIDENCE FROM SERBIAN - Bešlin, Maša (Годишњак Филозофског факултета у Новом Саду, 2023)
This paper examines the syntactic properties of the Serbian modal verb trebati ‘need’, which appears in the environment ‘NP – trebati ‘need’ – finite da-clause’. I show that trebati is a raising verb and that the preverbal NP is a (raised) subject. Trebati (φ-)agrees with the preverbal NP only optionally, which is surprising since other Serbian verbs agree with their subjects obligatorily. Furthermore, the subject is free to remain in the embedded clause, suggesting that the raising operation is not triggered by the need to satisfy unvalued features on matrix T (contra e.g., Chomsky 1981, 2008). I instead propose that A-movement (of this kind) is ‘free’; more precisely, it is fully optional, it can occur at any stage of the derivation (or not), and it is constrained only by the requirement that the output be well-formed. I show that this analysis accounts for the full range of data with trebati, but that it can also be applied to English-style raising constructions.